Design and Development of a Web-Based Multimedia Platform for the Promotion of LKP Karyaprima - Supiyandi Supiyandi; Abil Alwi Prayoga (Journal of Information Technology and Systems Engineering, 2026)
Lembaga Kursus dan Pelatihan (LKP) Karyaprima, like many small-scale non-formal vocational training providers, relied on conventional promotional methods that limited its reach, interactivity, and the presentation of its training programs to prospective learners. This study aimed to design, develop, and evaluate a web-based multimedia platform to support the promotion of LKP Karyaprima. The Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model was adopted as the research and development framework. Data were collected through interviews with institutional stakeholders, observation of existing promotional practices, documentation review, expert validation, and a usability evaluation combining the WebQual 4.0 instrument and the System Usability Scale (SUS). The resulting platform integrated an institutional profile, training-program descriptions, photo and video documentation, instructor and facility information, alumni testimonials, an online registration feature, and an administrative content-management module. Expert validation indicated that the platform met content- and media-feasibility criteria, while the usability evaluation indicated a favourable overall user experience across the usability, information-quality, and interaction-quality dimensions. The findings suggested that the platform had the potential to strengthen the promotional visibility and perceived attractiveness of LKP Karyaprima among prospective learners.